Induction motor stability analysis - Gupta Ravi. (2009)
Voltage stability has been an important issue to ponder on for a very long time in the Electric Power Industry. A power system can become unstable due to a sudden increase in the demand of power, a sudden disturbance like fault or fluctuation or any other change in system condition that can cause a decline in the system voltage. Induction motors are an essential part of any power system and many such motors are used in industrial environment far carrying out precise operations. These motors work on specific voltage range and any fluctuations in the power system can hamper their performance. Our main focus in this study would be on induction motor loads in power system and their voltage stability. In this dissertation, we are concerned about two things. One is the addition of compensation in the power system and studying its effect on the voltage level availability at the terminals of the induction motor load in faulty as well as non- faulty situations. The second part is about the analysis of the stability of the induction motor load in the power system which is a key clement in deciding the stability of the power system itself. This dissertation investigates the speed collapse process of the induction motor load in contest of varying fault voltages or the load torque requirement leading to its instability and disturbing the economics of costly industrial processes.